Breast cancer screening in transgenders: an integrative literature review (Research, Society and Development, 2022)
Introduction: Breast cancer, with the exception of non-melanoma skin cancer, is the most frequent in Brazil. Breast cancer is stratified into subtypes according to its genesis. Estrogen, in turn, is a steroid hormone that is related to the origin of hormone-dependent breast cancer. In this context, hormone therapy, used in the treatment of menopausal symptoms and also in hormone therapy for transgenders, is directly involved with the volume of estrogen circulating in the body of these groups. Objective: Given the above, there is concern about the increased incidence of breast cancer in transgenders. Therefore, this literature review aimed to evaluate the relationship between breast cancer and hormone therapy in the long term, and also, the status of breast cancer screening in women and transgender men, as well as its challenges. Methodology: Literary review, resulting from searches in VHL, PubMed, EbscoHost and SciELO covering articles in English, Portuguese and Spanish. Results: Twelve articles were analyzed. It was evidenced in the literature insufficient documentation for a possible affirmation or denial of the relationship between hormone therapy and higher incidence of breast cancer in transgenders, due to the lack of studies. Conclusion: It is necessary that the epidemiology be better understood, so that there is some proper guideline regarding secondary prevention in transgender people, in addition to better preparation of professionals for quality care. Still, it is suggested that this population be better documented, in order to have more studies and specific policies.